Left ventricular dysfunction causing ischemia in patients with patent coronary arteries. (March 2018) - Nguyen, Thach; Do, Hoang; Pham, Tri; Vu, Loc T; Zuin, Marco; Rigatelli, Gianluca
Background: New onset of heart failure (HF) is an indication for the assessment of coronary artery disease. The aim of this study was to clarify the mechanistic causes of new onset HF associated with ischemic electrocardiograph (EKG) changes and chest pain in patients with patent or minimally diseased coronary arteries. Methods: Twenty consecutive patients (Group A) were retrospectively reviewed if they had an history of new onset of HF, chest pain, electrocardiographic changes indicating ischemia (ST depression or T wave inversion in at least two consecutive leads and a negative coronary angiogram [CA]) and did not require percutaneous coronary intervention or coronary artery bypass grafting. A 1:1 matched cohort (Group B) was adopted to validate the results. Results: All patients had a negative CA. The majority of subjects in Group A had a higher left ventricular end diastolic pressure (LVEDP) when compared to the control group (p<0.05). Similarly, the aortic diastolic (AOD) pressure was lower in Group A than in Group B (p<0.05). In patients with elevated LVEDP and low AOD, with a coronary perfusion pressure (CPP) <20 mmHg, deep T wave inversion in two consecutive leads were more frequently observed. When the CPP was between 20-30 mmHg, a mild ST depression were more frequently recorded (p<0.05). Conversely, when the CPP was >30 mmHg, only mild non-specific ST-T changes or normal EKG were observed. Conclusions: In patients with HF and EKG changes suggestive of ischemia in at least two consecutive leads, a lower AOD could aggravate ischemia in patients with elevated left ventricular end diastolic pressure.